Genetic variation in Northern Thailand Hill Tribes: Origins and relationships with social structure and linguistic differences - Besaggio D. (2014)
Background. Ethnic minorities in Northern Thailand, often referred to as Hill Tribes, are considered an ideal model to study the different genetic impact of sex-specific migration rates expected in matrilocal (women remain in their natal villages after the marriage and men move to their wife's village) and patrilocal societies (the opposite is true). Previous studies identified such differences, but little is known about the possible interaction with another cultural factor that may potentially affect genetic diversity, i.e. linguistic differences. In addition, Hill Tribes started to migrate to Thailand in the last centuries from different Northern areas, but the history of these migrations, the level of genetic legacy with their places of origin, and the possible confounding effects related to this migration history in the patterns of genetic diversity, have not been analysed yet. Using both original and published data on the Hill Tribes and several other Asian populations, we focused on all these aspects. Results. Genetic variation within population at mtDNA is lower in matrilocal, compared to patrilocal, tribes. The opposite is true for Y-chromosome microsatellites within the Sino-Tibetan linguistic family, but Hmong-Mien speaking patrilocal groups have a genetic diversity very similar to the matrilocal samples. Population divergence ranges between 5% and 14% at mtDNA sequences, and between 5% and 36% at Y- chromosomes STRs, and follows the sex-specific differences expected in patrilocal and matrilocal tribes. On the average, about 2 men and 14 women, and 4 men and 4 women, are exchanged in patrilocal and matrilocal tribes every generation, respectively. Most of the Hill Tribes in Thailand seem to preserve a genetic legacy with their likely geographic origin, with children adoption probably affecting this pattern in one tribe. Conclusion. Overall, the sex specific genetic signature of different postmarital habits of residence in the Hill Tribes is robust. However, specific perturbations related to linguistic differences, population specific traits, and the complex migratory history of these groups, can be identified. Additional studies in different populations are needed, especially to obtain more precise estimates of the migration parameters. © 2007 Besaggio et al; licensee BioMed Central Ltd.